Awareness and Attitudes towards Influenza and Influenza Vaccination among Healthcare Professionals in Pakistan - Zeeshan Hassan, Farah Ahmad, Syed Hasan Danish (Pakistan Journal of Medical & Health Sciences, 2023)
Background:The coverage of the vaccine for health workers is not satisfactory. The study was conducted with health workers in a large community.A self-administered questionnaire was used based on "Awareness and Attitudes.Several factors may be related to influenza vaccination, and identifying these can support the development of policies and strategies that expand vaccination coverage. Aim: To identify vaccination-related factors based on awareness and attitudes, but priority is still scarce. Methods:It was a cross-section study among 349 healthcare workers to determine their attitudes and awareness toward the vaccine. The results were evaluated statistically to observe the significantassociation using the fisher’s exact/Chi-square tests respectively. A p-value <0.05 is taken as significant. Results:Three hundred and forty-nine responses were analyzed (190 men and 159 women). The average age of vaccines was 41.10±11.90 years. 186(53.2%) patients aged>40 yrs, while the majority of 263(75.4%) of the study group were physicians, 78(22.3%) were pharmacists, and only 5(1.4%) were nurses. A percentage increase was seen of healthcare professionals from private set-upwho wereless susceptible to influenza 109(59.6%) compared to other HCPs in public sector, GP clinics and vaccination centers(P=0.010*). Practical implication: Healthcare professionals with a good attitude about the flu shot are more likely to receive the shot themselves and encourage their coworkers and patients to do the same. This can increase overall vaccination rates and assist in stopping the influenza virus from spreading.Healthcare workers are more likely to take preventative measures to stop the transmission of the virus, such as wearing masks and washing their hands, if they are informed of the risks of influenza and the advantages of vaccination. Conclusion:There is a lack of awareness about the nosocomial nature of influenza among HCPs. Awareness and counseling can increase in the vaccination rate among healthcare workers. Keywords:Influenza vaccination, Healthcare workers,attitudes and knowledge